Evaluation of Early Growth Traits and Herbage Biomass Production of Selected Oat Genotypes Under Different Sowing Dates - Regmi, Saroj; Devkota, Naba Raj; Ghimire, Ram Prasad; Barsila, Shanker Raj (Journal of Agriculture and Forestry University, 2026)
Early growth traits are important indicators of plant vigor and potential herbage yield. Lack of knowledge on how early growth traits respond to different sowing dates and their influence on herbage biomass is limiting oat fodder production in the Terai region. Optimum sowing date can enhance livestock feed availability and quality through higher herbage biomass production. The objective of this study was to evaluate early-stage growth attributes and herbage yield under different sowing dates. A field experiment was conducted using a two-factor factorial randomized complete block design with four replications at Rampur, Chitwan. Four oat genotypes (Nandini, Amritdhara, Swan Pak, and Longford) were sown on three dates: 1 November, 15 November, and 30 November. Significant differences (p<0.05) were observed among genotypes and sowing dates for all the studied traits. Nandini, Swan Pak, and Amritdhara showed the highest tillering, while leaf number and leaf area were greatest at 15 November sowing. Longford had the highest chlorophyll content. Amritdhara produced the highest dry matter yield (2.53 t ha-1), followed by Swan Pak (2.49 t ha-1), with maximum yield observed at 15 November sowing (2.64 t ha-1). Plant height and tiller number contributed most positively to dry matter yield. Sowing Swan Pak and Amritdhara on November 15 holds potential for higher fodder production under the agro-climatic conditions of the Inner Terai region of Nepal. Further multiyear trials are recommended to validate these findings and utilize them in agronomic practices.